The impact of a plastic ban implementation scenario on residents of Tiruchirappalli region - Siddeshwar, Kavya; Devi, M. Prashanthi (Acta Geographica Debrecina Landscape & Environment series, 2023)
Plastic was created first for its durability, extended life, and capacity to be moulded into a broad range of items. There are three reasons why plastics are still used in the packaging sector, even though they are harmful to the environment. First, its low economic cost and widespread circulation. The second feature is their capacity to contain air and water while remaining watertight. The third characteristic is its relative inertness. Based on this, respondents were polled to assess their awareness of alternatives and to comprehend the pre- and post-ban situation for plastics. About 370 respondents from different age groups from different sectors from urban and rural dwellers of Trichy were asked about the prohibition of plastic carry bags, its acceptance, the alternatives available and the cost paid. Most respondents were unhappy about the removal of plastic bags and the high cost of cloth or other bags. Due to environmental concerns and their implications, it was revealed that the negative effects of plastics had not entered society sufficiently to allow the people to reject them. However, durability, lightness, flexibility, and low cost still predominate because the consumer requires plastic bags. Strict steps aiming at promoting public knowledge of the damaging consequences of plastics, their negative impact on the environment, and lowering the costs of alternatives should be explored as immediate remedies.